(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Al-Kraety IAA, Al-Muhanna SG, Banoon SR, Ghasemian A. 2022. Bacterial vaginosis pattern and antibiotic susceptibility testing in female patients using high vaginal swabs. Biodiversitas 23: 2838-2844. Bacterial species found in the vaginal environment encompass a wide variety of species. A common cause of vaginal discharge in women is bacterial vaginosis BV (BV). Various Gram-positive and Gram-negative rod shaped bacteria, including E. coli, Klebsiella spp., Enterococcus spp., Enterobacter spp., Raoultella ornithinolytica, and Staphylococcus spp. contribute significantly to bacterial vaginosis. In this study, vaginal swabs (VS) were obtained from 50 individuals with symptoms of vaginal discharge. The swabs were inoculated on blood, Mannitol, and MacConkey agar culture media. Biochemical tests were performed after an overnight incubation period to determine growth and colonial morphology. In addition to VITEK® 2 compact system and PCR technique by using a 16s RNA gene where all bacteria isolates were positive for this gene. Antibiotic sensitivity was investigated through compact VITEK® 2 and sensitivity cards (AST-P580), (AST-N222), and (AST-GN76). The bacterial isolates including 20 (43.4%) of E. coli, 8 (17.3%) of Klebsiella spp. and 8 (17.3%) of Staphylococcus spp. were investigated in present study. Additionally, 4 (8.6%) isolates of Enterobacter spp., 3 (6.5%) of E. faecalis, and 3 (6.5%) of R. ornithinolytica. The E. coli, Staphylococcus spp., Enterobacter spp., E. faecalis and R. ornithinolytica isolates were found resistant to several antibiotics and considered multi-resistance (MDR).